Effects of mobile apps intervention on medication adherence and type 2 diabetes mellitus control: A systematic review and meta-analysis - Chong, Cheng Jun; Bakry, Mohd Makmor; Hatah, Ernieda; Mohd Tahir, Nor Asyikin; Mustafa, Norlaila (Journal of telemedicine and telecare, 2025)
The prevalence of non-adherence to antidiabetic treatment remains high despite various efforts. Thus, the positive effects of the antidiabetic treatment cannot be optimised and the disease progresses to complications. This present systematic review and meta-analysis aimed to evaluate the effects of mobile applications (apps) intervention on medication adherence and type 2 diabetes mellitus (T2DM) control. This research was conducted following the PRISMA guidelines. The databases that had been searched included Web of Science, PubMed, Scopus, Cochrane Library and Ovid from 2017 to 2022. Study characteristics were retrieved and study outcomes such as adherence status and diabetes control were extracted and quantitatively analysed through meta-analysis. Eight studies met the final inclusion criteria and were included in the analysis, contributing to a total of 884 subjects. The methodological quality of the included studies was variable. Three studies reported statistically significant improvement in medication adherence through mobile apps intervention. Additionally, the mobile apps intervention proved effective in reducing glycaemic outcomes. As compared to non-mobile apps users, glycated haemoglobin (HbA1c) significantly decreased by 0.36% (95% CI -0.47% to -0.25%), whereas fasting plasma glucose (FPG) significantly decreased by 16.75 mg/dL (95% CI -17.60 mg/dL to -15.80 mg/dL). Mobile apps intervention had beneficial impacts on medication adherence and glycaemic parameters. Future research should explore the best practical approach for real-world settings.